The Association of Having a Late Dinner or Bedtime Snack and Skipping Breakfast with Overweight in Japanese Women - Chika Okada; Hironori Imano; Isao Muraki; Keiko Yamada; Hiroyasu Iso (Journal of Obesity)
Background. We aimed to assess the association of habitually eating in the late evening and skipping breakfast with the prevalence of overweight/obesity. Methods. A total of 19,687 Japanese women, aged 40–74 years, were asked about their height, weight, and habitual eating behaviors such as having a late dinner and a bedtime snack and skipping breakfast, using a self-administered questionnaire. We defined overweight/obesity as body mass index greater than or equal to 25 kg/m2. Results. Among the participants, 11% regularly had a late dinner, 22% had bedtime snacks, and 8% skipped breakfast. After adjusting for age, exercise, smoking, sleep duration, and employment, the multivariable-adjusted odds ratios (ORs) and 95% confidence intervals (CIs) of skipping breakfast were 2.47 (2.18–2.81) for having a late dinner and 1.71 (1.53–1.91) for having a bedtime snack. These eating behaviors were associated with an increased risk of overweight/obesity: the multivariable-adjusted ORs (95% CIs) of obesity/overweight were 1.43 (1.27–1.62) for having a late dinner, 1.47 (1.34–1.62) for having a bedtime snack, and 1.23 (1.06–1.42) for skipping breakfast. Conclusions. Japanese women who consumed late dinners or bedtime snacks were more likely to skip breakfast. Having a late dinner or bedtime snack was associated with a higher probability of overweight/obesity.